Analisis Price to Book Value, Current Ratio, Return On Equity, Dan Debt To Equity Ratio Terhadap Harga Saham - Apriliani Sya’diah; Nor Norisanti; Asep Muhamad Ramdan (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
This study is to analyze the effect of Price to Book Value (PBV), Current Ratio (CR), Return On Equity (ROE), and Debt to Equity Ratio (DER) on stock prices for various industrial sector companies listed on the Indonesia Stock Exchange (IDX). ) the time span 2018 - 2020. The population in this study are companies that have been listed on the Indonesia Stock Exchange (IDX) in 2018 -2020. The research sample is 10 companies in various industrial sectors which were found using a purposive sample technique. The method used in this research is descriptive analysis test, classical assumption test, multiple linear regression, T test and F test to get results regarding the effect of the independent variable on the dependent variable. The results of this study indicate that partially Price to Book Value (PBV) has a significant effect on stock prices, while the Current Ratio (CR), Return On Equity (ROE), and Debt to Equity Ratio (DER) have no significant effect. Simultaneously, the variables Price to Book Value (PBV) Current Ratio (CR), Return On Equity (ROE), and Debt to Equity Ratio (DER) affect stock prices. The results of the coefficient of determination (R2) show that the variables PBV, CR, ROE, DER have a large influence of 87.4% on stock prices, while the remaining 12.6% is influenced by other variables not examined in this study. Keywords : Price to Book Value, Current Ratio, Return On Equity, Debt to Equity Ratio, and Stock Price